Student-centred learning (SCL): roles changed? - Aliusta, Guelen Onurkan; Ozer, Bekir (Routledge Journals, Taylor & Francis Ltd, 2017)
This paper addresses the espoused and enacted practices of high school teachers with regard to student-centred learning (SCL). Explanatory mixed-method design, where quantitative strand is followed by qualitative one, is employed. While the quantitative strand aims to explore teachers' perceptions regarding the extent student-centred teacher and student roles are performed, qualitative strand is used to explore how well the enacted roles represent the espoused ones and to explain the discrepancies, if any, between them. The findings indicate discrepancies between espoused and enacted practices of teachers. Qualitative data reveal that teachers' beliefs about teacher and student roles are still very much teacher centred. Reasons are varied including system-wide barriers hindering the adoption of SCL and teacher training offered. The findings draw attention to an urgent need for alternative teacher training programmes that would focus on changing teachers' traditional beliefs enabling them to put theory into practice and adopt student-centred roles.
Keywords: Student-centred learning; teacher roles; student roles; educational change